The efficacy of environmental enrichment as cognitive enhancer : an evaluation of the underlying mechanisms - Birch, Amy (Trinity College (Dublin, Ireland). Department of Physiology, 2012)
Environmental manipulations can enhance neuroplasticity in the brain, with enrichment- induced cognitive improvements being linked to increased expression of growth factors, such as neurotrophins, and enhanced hippocampal neurogenesis. Environmental enrichment can ameliorate the memory decline reported in normal ageing and in animal models of Alzheimer’s disease, Huntington’s disease and depression. Thus, this may be a particularly beneficial therapeutic intervention against age-related cognitive decline. Environmental enrichment is defined as the addition of social, physical and somatosensory stimulation into an animal’s environment via larger group housing, extra objects and often, running wheels. Previous studies from our lab report that physical activity alone is a potent memory enhancer but that long-term environmental stimulation can be as effective as exercise at ameliorating age-related memory decline. Therefore, it is crucial to dissociate the different factors of environmental enrichment, and to elucidate the associated neurochemical mechanisms. The aim of this study is to evaluate the efficacy of environmental enrichment, in the absence of exercise, as a cognitive enhancer and assess the underlying mechanisms involved, with particular focus upon the roles of neurotrophins and neurogenesis in mediating this effect.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin